Ordination of gay men: Canon 1041 - Golden, Paul L. (Roman Replies and CLSA Advisory Opinions 2006, 2006)
"As a vocation director of a religious institute of men, I am charged with recommending candidates to begin their studies for the priesthood. What is the canonical import of the recent Instruction of the Congregation for Catholic Education regarding gays entering the seminary and being ordained? Do we have a new irregularity to the reception of orders?"